The effect of acupressure therapy on the ciliary point (BL32) and lavender aromatherapy on reducing the intensity of labor pain - Veryudha Eka Prameswari; Indra Yulianti (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Childbirth is a joyous experience, but that joy can turn into anxiety and pain when contractions become more intense. Mothers about to give birth experience pain and discomfort due to uterine contractions that initiate the labor process. Efforts to reduce the intensity of pain in mothers giving birth can be done by using acupressure therapy at the BL 32 point and lavender aromatherapy. The purpose of this study was to examine the effect of acupressure therapy at the ciliao point (BL32) and lavender aromatherapy on reducing the intensity of labor pain. The study was conducted on August 27 - October 7, 2025. This study used a pre-experimental method with a pre-test and post-test. The study population was mothers giving birth in the active phase of the first stage. The sampling technique used was accidental sampling with 16 respondents. The results of the study were that almost all pain scales before being given a massage of the BL 32 point and lavender aroma therapy were 9.06 with a standard deviation of 0.772, and after being given a massage of the BL 32 point and lavender aroma therapy were 7.56 with a standard deviation of 0.814. The Wilcoxon Signed Ranks test results ρ = 0.00, so the conclusion is that there is an effect of giving BL 32-point therapy and lavender aroma therapy on reducing the intensity of labor pain.